Analisis Kesulitan Pembelajaran Pendidikan Jasmani Adaptif di SLB C dan C1 Yakut Purwokerto - Nuraini, Febrina Shelfa Dwi; Yuwono, Cahyo (Indonesian Journal for Physical Education and Sport, 2023)
The research background is that difficulties in learning with special needs are often ignored so that the need for physical education for children with special needs is not good and will also have an impact on the physical health of children with special needs. The purpose of this study is to describe the difficulties in learning physical education for mental retardation classes at SLB C and C1 Yakut Purwokerto. This type of research is using qualitative research. The subjects in this study were sports teachers and mentally retarded students at SLB C and C1 Yakut Purwokerto. Methods of data analysis in research using observation, interviews and documentation. Data analysis using data reduction, data presentation and conclusion. The results of the study obtained that Adaptive Physical Education learning at SLB C and C1 Yakut Purwokerto took place according to the existing learning schedule and hours. Teachers teach according to the competencies that must be achieved by students. However, in adaptive learning the teacher does not always meet conducive learning conditions and experiences difficulties in teaching existing basic competencies. This can be influenced by internal and external factors from students. The conclusion is that adaptive physical education learning goes according to schedule but there are several obstacles both from internal and external factors.